BUSINESS PARTICIPATION IN IMPLEMENTATION OF SOCIALLY ORIENTED SUSTAINABLE DEVELOPMENT GOALS IN COUNTRIES OF CENTRAL ASIA AND THE CAUCASUS REGION - ZAVYALOVA, Elena; STUDENIKIN, Nikolay; STARIKOVA, Evgeniya (CENTRAL ASIA AND THE CAUCASUS, 2018)
The authors have concluded that the degree of engagement of the business community in resolving sustainable development issues is one of the primary factors of its long-term competitiveness. The paper discusses topical private projects and initiatives aimed at attainment of socially oriented Sustainable Development Goals as delineated in the U.N. document in 2015.